Study on the Morpho-physiological Character of Four Quality Protein of Maize (Corn) (Journal of Environmental Science and Natural Resources, 2017)
The experiment was conducted to find out the morpho-physiological variability in response to different sowing dates in four lines of Quality Protein Maize (QPM) in in the Field Laboratory of the Department of Crop Botany, Bangladesh Agricultural University, Mymensingh. The study was carried out with four lines of maize and two sowing dates, 15 November (T1) and 15 December, ((T2). Sowing date differed significantly in plant height, length of leaf blade, length of leaf sheath, leaf breadth, cob length, cob diameter, length of tassel, days to 50% tasselling, days to 50 % silking, days to maturity, number of cobs per plant, cob weight, number of grain per cob. 1000-seed weight, percent underdeveloped cob, total dry matter and grain yield, but did not differ in number of leaves and protein percent. The lines differed significantly among themselves in those characters except number of leaves per plant, length of leaf sheath, cob length, cob diameter, days to 50% tasselling, number of cobs per plants and number of grain per cob. The line Across 8666 (V2) and (V3) gave the highest grain yield 4.57 and 4.55 and the lowest from (V4) lines 4.41 tons per hectare. The 15 November sowing time (T1) gave the highest grain yield 4.86 tons per hectare. In case of interaction, the earlier planting time (T1) showed better performance with all lines. On the other hand, the highest yield was found from combination of line V2 and V3 with earlier planting time (T1).J. Environ. Sci. & Natural Resources, 10(1): 117-124 2017